Lipid oxidation in foods and its implications on proteins - Geng, Lianxin; Liu, Kunlun; Zhang, Huiyan (Frontiers in Nutrition, 2023)
Lipids in foods are sensitive to various environmental conditions. Under light or high temperatures, free radicals could be formed due to lipid oxidation, leading to the formation of unstable food system. Proteins are sensitive to free radicals, which could cause protein oxidation and aggregation. Protein aggregation significantly affects protein physicochemical characteristics and biological functions, such as digestibility, foaming characteristics, and bioavailability, further reducing the edible and storage quality of food. This review provided an overview of lipid oxidation in foods; its implications on protein oxidation; and the assessment methods of lipid oxidation, protein oxidation, and protein aggregation. Protein functions before and after aggregation in foods were compared, and a discussion for future research on lipid or protein oxidation in foods was presented.